Uso do percarbonato de sódio como alternativa ao peróxido de hidrogênio na oxigenação emergencial da água e em tanques com juvenis de tilápia do Nilo, oreochromis niloticus - Portela, Breno José Sousa (2022)
The objective of this work was to verify the physicochemical effects of the application of hydrogen peroxide and the alternative product sodium percarbonate (SPC) for the emergency oxygenation of deoxygenated water and in tanks with Nile tilapia (Oreochromis niloticus) juveniles induced to hypoxia, in addition to determining the safe range of application of these products for this species. The work consisted of three phases. In the first phase, 20 tanks were filled with 100 L of water from the public supply system. The water in the tanks was initially deoxygenated by applying 5 mg L-1 of sodium sulfite p.a. and about 0.25 g of cobalt chloride p.a. When the dissolved oxygen concentration in the water was reduced to 2.44 ± 0.04 mg L-1 , emergency oxygenation products were applied. It consisted of five treatments with four replications: tanks without the application of any emergency oxygenation product; with application of 1.5 mL of peroxide and hydrogen 35% p.a.; with application of SPC 0,10; 0,20 and 0,50g/100L respectively. The following physical-chemical determinations of water quality were performed every half hour, during three hours of monitoring: pH, dissolved oxygen, temperature and total alkalinity. In the second stage, twenty-four tanks were filled with 100 L deoxygenated in the same way as in the first stage. Six treatments were constituted, with four replications each, being, therefore: tanks without application of any emergency oxygenation product; with application of 3.0 mL of hydrogen peroxide 35% p.a.; with mechanical aeration point; with application of SPC 0,10; 2,43 and 4,86 g/100L respectively. The pH, dissolved oxygen, temperature and total alkalinity were evaluated every hour for five hours. In the third stage, twenty-four tanks with 100 L and six fish in each were filled, constituted with the same treatments, repetitions and physicochemical determinations of the second stage. For water deoxygenation, 10 ± 0.3g of commercial feed was applied at the beginning and the air compressor was stopped in all treatments. When the dissolved oxygen concentration in the water was reduced below 4 mg L-1 , emergency oxygenation products were applied and the compressor was turned on only for mechanical aeration point treatment. In the first stage, no treatment reached the minimum oxygen recommendation for tropical fish and had little influence on the other variables. In the second phase the SPC with the highest concentrations showed similar effects to mechanical aeration and both were superior between treatments, however the SPC increased the pH and alkalinity. Nile tilapia juveniles were not affected by the dosage used and high SPC rates along with mechanical aeration were better at oxygenating the water, SPC raised the pH and alkalinity which were still in the recommended range. It was concluded that the SPC at higher doses showed efficiency similar to mechanical aeration and better than hydrogen peroxide, being able to be used up to 4,86g/100L for emergency oxygenation of tanks with Nile tilapia juveniles.